Efforts to Improve Teachers' Ability in Using Learning Media Through Supervision Techniques for Class Visits - Cendra Krida (Syntax Corporation Indonesia, 2021)
The low quality of human resources, especially educators/teachers, is one of the main problems in the world of education. Like the fact that happened at SDN 001 Seri Kuala Lobam, especially the use of media in learning activities in the past year, based on the results of the supervision of the principal on 6 teachers, it was found data that in the implementation of learning teachers did not use media. The teacher explains more about the material even though the material can be clarified with easily available media, both media available at school and around the school. Of the 21 teachers at SDN 001 Seri Kuala Lobam only 5 people (25%) have used media in learning activities while 16 people (75%) still do not use media. With these problems, it must be immediately addressed by efforts to increase the ability to supervise teachers with inter-class visits. The inter-class visit technique is an activity carried out by one teacher visiting another class in the school environment itself. This inter-class visit can be done individually between teachers or a group of teachers visit a teacher. Through these inter-class visits, it is hoped that teachers will gain new experiences from their more professional peers. School Action Research (PTS) with the subject of teachers at SDN 001 Seri Kuala Lobam, Seri Kuala Lobam District, amounted to 41 people. This research was carried out in two action cycles with 2 meetings in each cycle. In each cycle, there are planning, implementation, observation, and reflection activities. The instrument used is an observation sheet. Observational data were analyzed descriptively qualitatively and descriptively by quantitative percentages. The results showed an increase in the teacher's ability to use learning media wherein cycle 1, meeting 1 was 60% in the sufficient category, increased at meeting 2 to 67% in the good category. In cycle 1I, meeting 1 increased to 75% in the good category and there was an increase at meeting 2 to 85% in the very good category. Implementation of supervision with inter-class visits technique in cycle I meeting 1 was 64% with good category increasing to 76% with the good category at meeting 2, In cycle 2 meeting 1 increased again to 81% with very good category and at meeting 2 to 88% with very good category.